Is downsizing prisons dangerous?: the effect of california's realignment act on public safety - Sundt, Jody L. (Criminology & public policy, 2016)
Recent declines in imprisonment raise a critical question: Can prison populations be reduced without endangering the public? This question is examined by testing the effect of California's dramatic efforts to comply with court‐mandated targets to reduce prison overcrowding using a pretest‐posttest design. The results showed that California's Realignment Act had no effect on violent or property crime rates in 2012, 2013, or 2014. When crime types were disaggregated, a moderately large, statistically significant association between Realignment and auto theft rates was observed in 2012. By 2014, however, this effect had decayed and auto theft rates returned to pre‐Realignment levels.